Intensitas Riset dan Pengembangan untuk Peningkatan Kinerja Keuangan Melalui Inovasi Produk Ramah Lingkungan - Izzaty, Khairina Nur; Atiningsih, Suci (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The financial performance of manufacturing companies depends on how capable the company is of continuing to innovate to produce quality and environmentally friendly products in order to gain customer trust. This innovation certainly requires in-depth research and development with adequate costs and intensity. Therefore, this research aims to analyze the influence of research and development intensity carried out by companies in encouraging environmentally friendly product innovation which is ultimately able to increase profitability as an illustration of the company's financial performance. The sample used for this research is manufacturing companies listed on the BEI in 2020 - 2022. This research uses quantitative research with secondary data, namely annual reports and financial reports from the idx.co.id website. The results of this research found that: (1) research and development intensity has a positive effect on financial performance; (2) research and development intensity has a significant positive effect on environmentally friendly product innovation; (3) environmentally friendly product innovation has a significant positive effect on financial performance; (4) environmentally friendly product innovation is able to partially mediate the influence of research and development intensity on financial performance